(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Gestational diabetes mellitus (GDM) is an important cause of maternal and perinatal morbidities. Vitamin D is associated with glucose metabolism. The present study was aimed to assess the association of maternal serum vitamin D level with GDM. This case-control study was conducted among 80 pregnant women at the Department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Among the 80 patients, 40 were GDM patients (cases) and 40 pregnant women without GDM (controls). The serum vitamin D level was measured for all of them. The mean vitamin D level of the cases and controls were 18.8±5.5 ng/ ml and 22.1±7.3 ng/ml, respectively (P=0.025). There was significant difference regarding the vitamin D adequacy in between case and control groups (P= 0.006) and the respondents with vitamin D <30.0 ng/ml had 7.2 times more chances to have GDM compared to that of the respondents with vitamin D ≥30 ng/ml (OR=7.2; 95% confidence interval =1.5-35.1). There was a significant negative correlation between serum vitamin D level and plasma glucose level 2-hour after 75 gm glucose drink (r= -0.33, P= 0.004). In conclusion, serum vitamin D level was found low in patient with GDM compared to those without GDM. BSMMU J 2022; 15(3): 162-166